COMPOSICIÓN Y ESTRUCTURA DE LA VEGETACIÓN BOSCOSA DE LA CUENCA BAJA DEL RÍO SAN SALVADOR, VERTIENTE NORTE DE LA SIERRA NEVADA DE SANTA MARTA, COLOMBIA - A. Dechner; M. Diazgranados (Universitas Scientiarum)
In this research, floristic composition and structure of vegetation of forests in the low basin of the SanSalvador River (Sierra Nevada de Santa Marta) were studied. Through the analysis of a satellite imageIKONOS, two types of forested cover were identified. Fifteen sample areas of 0.1 ha (15 000 m2) werelocated in the largest fragments of forest. 809 individuals with DBH = 10cm, belonging to 74 species and33 families were registered. According to the results, species diversity in the area is low with regard toother moist tropical forests and species richness varied from 7 to 19 species per plot. Distribution ofindividuals in DBH classes showed in the majority of sampled areas an inverted “J” shape trend, as it hasbeen reported in other tropical forests. The richest genera in terms of species were: Brosimum (Moraceae),Ficus (Moraceae), Licania (Chrysobalanaceae), Saurauia (Actinidiaceae) and Vismia (Guttiferae), eachof them with 2 species. These results represent a successful first phase to establish priorities for conservationof San Salvador river basin.